"Being a butt while on the internet": Perceptions of what is and isn't internet trolling. Issue 1 (1st February 2019) - Chen, Yimin
ABSTRACT: The term "internet trolling" has come to encompass a wide range of behaviours, ranging from abusive speech and hacking to sarcastic humour and friendly teasing. While some of these behaviours are clearly antisocial and, in extreme cases, criminal, others are harmless and may even have potential prosocial functions. This study is an attempt to disambiguate some of the competing and contrary interpretations of internet trolling by examining the perspectives of avid internet users for whom trolling is a familiar part of their online lives. Through data collected from in‐depth, semi‐structured interviews, a multifaceted picture of trolling emerges that is at odds with previous media characterizations of internet trolls as merely hateful bullies. On the contrary, most participants in this study did not consider trolling to be a serious problem and many did not consider harmful interactions to be trolling at all. This paper describes some of the defining characteristics of internet trolling in order to differentiate the harmful behaviours from the harmless. This work aims to contribute to the growing body of literature on internet trolling in the hopes of informing regulatory policy and educational initiatives concerning internet use and safety.